Integrasi Zakat sebagai Reformulasi Kebijakan Fiskal Indonesia Berbasis Syariah dengan Prinsip Ekonomi Islam - Saini, Saini; Hasan, Zaenol (Journal of Economic and Business Law Review, 2024)
As an essential part of Islamic economic instruments, Zakat has a strategic role in supporting Sharia-based fiscal policies in Indonesia. Integrating Zakat into fiscal policy can strengthen budgetary sustainability and improve social justice through wealth redistribution, economic empowerment, and poverty alleviation. This study explores the potential of Zakat in supporting the reformulation of a more inclusive and equitable fiscal policy. The method used in this study is thematic with a library research approach, reviewing literature on Zakat, budgetary policy, and Islamic economics. The study results show that Zakat contributes to the equitable distribution of wealth and empowers the economy through transparent and accountable management. Zakat also plays a role in strengthening collaboration with financial authorities to improve the efficiency of its collection and distribution. The principles of Islamic economics, such as social justice, multi-type ownership, and equitable distribution, provide a strong foundation for efficient and inclusive resource management. This study recommends optimizing Zakat through digital technology and strengthening synergy between institutions for more effective zakat management.